The impact of organizational commitment on job performance in primary healthcare: a motivation internalization perspective - Zhao, Shichao; Wang, Tao; Luo, Shanshan; Mi, Yuequn; Wang, Ying; Ma, Huifen; Wei, Xiaolin (Frontiers in Public Health, 2025)
IntroductionPrimary healthcare workers (PHCWs) are crucial to the healthcare system, as they directly impact the delivery of essential health services. Their job performance is influenced by various types of organizational commitment, but the effects of these commitments are not fully understood. This study aims to explore how four types of organizational commitment (affective, normative, economic, and opportunity) affect job performance among PHCWs, using Self-Determination Theory to examine motivation internalization as a mediating factor.MethodsA cross-sectional survey of 870 PHCWs from 38 primary healthcare institutions was conducted. Hierarchical regression analysis was used to explore the relationships between commitment types, motivation internalization, and job performance.ResultsAffective and normative commitments positively predicted job performance, with motivation internalization partially mediating this relationship. Opportunity commitment negatively predicted job performance, mediated by reduced motivation internalization. Economic commitment showed no significant effect on either motivation internalization or job performance.DiscussionThe impact of organizational commitment on job performance is shaped by its motivational quality. Strengthening affective and normative commitments through supportive incentive strategies can enhance PHCWs’ performance in primary healthcare settings.